2002
DOI: 10.1007/s10103-002-8262-9
|View full text |Cite
|
Sign up to set email alerts
|

Changed Skin Blood Perfusion in the Fingertip Following Acupuncture Needle Introduction as Evaluated by Laser Doppler Perfusion Imaging

Abstract: Rapidly repeated imaging of the left middle fingertip skin blood perfusion was performed in 51 healthy volunteers (mean age +/- SD: 25.3 +/- 7.6 years) prior to, immediately after and in the early reperfusion phase following introduction of an acupuncture needle at the Neiguan point (Pe. 6) and at a placebo point respectively, using a Laser Doppler Perfusion Imager (LDPI). The average skin perfusion of the fingertip was calculated for each image and used as an indicator of the microvascular response to the acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 13 publications
1
54
0
1
Order By: Relevance
“…[3][4][5] In Traditional Chinese Medical (TCM) theory, the effects of acupuncture depend on the special sensation in a local acupoint after stimulation, which might be related to the blood perfusion changes in acupoints or meridians. 6 When an acupoint was stimulated adequately, the blood perfusion of this point continued to increase whereas the blood perfusion of the nonacupoint only changed slightly by the same acupuncture stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In Traditional Chinese Medical (TCM) theory, the effects of acupuncture depend on the special sensation in a local acupoint after stimulation, which might be related to the blood perfusion changes in acupoints or meridians. 6 When an acupoint was stimulated adequately, the blood perfusion of this point continued to increase whereas the blood perfusion of the nonacupoint only changed slightly by the same acupuncture stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the differences were not significant, temperature was 0.6°C higher in animals submitted to AqP. Previous reports showed that according to thermography, both AP and EA analgesia reduces sympathetic vasomotor activity and increases superficial skin temperature (ERNST; LEE, 1985;LITSCHER et al, 2002;THOMAS et al, 1992).…”
Section: Discussionmentioning
confidence: 75%
“…The data suggest that acupuncture induces amelioration of both myelin sheath and axon function. It has been shown by Litscher et al [3] that acupuncture may increase blood flow in the limbs. Increased blood flow to the vasa nervorum and dependant capillary beds supplying the neurons may potentially contribute to nerve repair with measurable improvement of axons or myelin sheaths after 10 treatments [4,5] .…”
Section: Discussionmentioning
confidence: 97%